The Role of Dissemination in Market Liquidity: Evidence from Firms' Use of Twitter™ - Blankespoor, Elizabeth; Miller, Gregory S.; White, Hal D. (The Accounting Review, 2014)
ABSTRACT Firm disclosures often reach only a portion of investors, which results in information asymmetry among investors and, therefore, lower market liquidity. This issue is particularly salient for firms that are not highly visible, as they tend not to receive broad news dissemination via traditional intermediaries, such as the press. This paper examines whether firms can reduce information asymmetry by more broadly disseminating their news. To isolate the impact of dissemination, we focus our analysis on firms' use of Twitter and exploit the 140-character message restriction. Specifically, using a sample of technology firms, we examine the impact of using Twitter to send market participants links to press releases that are provided via traditional disclosure methods. We find this additional dissemination of firm-initiated news via Twitter is associated with lower abnormal bid-ask spreads and greater abnormal depths, consistent with a reduction in information asymmetry. Moreover, this result holds mainly for firms that are not highly visible, consistent with them being in greater need of this additional dissemination channel. We also examine the impact of dissemination on a volume-based measure of liquidity, and find that dissemination is positively associated with liquidity. Data Availability: All data are publicly available from the sources indicated in the paper.